(E)-3-(2-Chlorophenyl)-1-(2,4-dichlorophenyl)prop-2-en-1-one - Fun, Hoong-Kun (International Union of Crystallography, 2008)
In the title chalcone derivative, C(15)H(9)Cl(3)O, the dihedral angle between the 2-chlorophenyl and 2,4-dichlorophenyl rings is 41.79 (14)°. Weak C—H⋯O and C—H⋯Cl intramolecular interactions involving the enone unit generate S(5) ring motifs. In the crystal structure, the molecules are arranged in a head-to-tail manner along the a axis. These chains are stacked along the b axis.